2009
DOI: 10.1111/j.1349-7006.2009.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the miR‐106b‐25 microRNA cluster in hepatocellular carcinoma

Abstract: MicroRNAs are tiny RNA molecules which serve as important posttranscriptional regulators of gene expression. Dysregulated expression of microRNAs has been observed in human cancers, indicating that microRNAs may function as oncogenes or as tumor suppressors. To date, the microRNAs encoded by the oncogenic miR-17-92 cluster, and its paralog the miR-106b-25 cluster, are among those which are differentially expressed in human cancers. In this study, we examined and confirmed the over-expression of these clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
195
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(208 citation statements)
references
References 62 publications
12
195
0
Order By: Relevance
“…The mir106b cluster is embedded within the MCM7 gene, which is a direct RB/E2F target gene. 16,[26][27][28][29][30] The mir106b cluster targets the expression of several genes that are directly disease-relevant and that provide a mechanism for cross-talk from the canonical RB pathway to PTEN and p21…”
Section: Discussionmentioning
confidence: 99%
“…The mir106b cluster is embedded within the MCM7 gene, which is a direct RB/E2F target gene. 16,[26][27][28][29][30] The mir106b cluster targets the expression of several genes that are directly disease-relevant and that provide a mechanism for cross-talk from the canonical RB pathway to PTEN and p21…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BH3-only proteins, BMF and BID, are targeted by miR-221 and miR-25, respectively. 29,30,43 These mechanisms have the potential to allow miR-221 to protect cells from 'anoikis', a form of apoptosis induced by the detachment of anchorage-dependent cells from the surrounding extracellular matrix. MiR-25 may also impair the TGF-b tumor suppressor pathway.…”
Section: 3mentioning
confidence: 99%
“…CDKN1A/p21 is downregulated by oncogenic members of the miR-17-92 family. [29][30][31][32][33] Among the three clusters of the miR-17-92 family of the human genome, those on chromosomes 13 and 7 are upregulated in HCC. 34 Disruption of apoptosis in HCC has been extensively reviewed.…”
Section: 3mentioning
confidence: 99%
“…Thus, there are urgent needs to develop novel therapeutic approaches by targeting the molecules that are altered in this malignancy. Recent studies showed that miR-25, a member of miR-106b clusters was frequent deregulated in a variety of cancer types (7)(8)(9). So far, there are few reports on miR-25 in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%